Integration of solar dryer technologies in high value herbal crops production for Malaysia: pathway for a sustainable future - Othman, Noor Fadzlinda; Ya'acob, Mohammad Effendy; Abdul Samad, Abdul Rahim; Othman, Mohd Shahwahid; Hizam, Hashim; Ramlan, Mohd Fauzi (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2016)
This paper embarks on the evolution of green economy approach to support the increasing food commodity expenses by adapting Solar Photovoltaic (PV) as the suitable renewable energy technology for Natural Resource Management (NRM). The crops for cash trend and continuously decreasing market price in solar technologies are highlighted with strong effort by Malaysian Government through Renewable Energy (RE) policy and National Key Economy Area (NKEA). Reviews on the benefits of solar dryer technologies in crop production and agro-business are presented with highlights on high value herbal crops (HVHc) and some potentials of high-performance solar dryer technology.